Citra (Image) Perempuan sebagai Objek Seksualitas dalam Iklan Studi Kasus Iklan Axe - Rukiah, Yayah (Magenta | Official Journal STMK Trisakti, 2017)
Television commercials began in 1947 in the form of sponsorship advertisements. Advertising is one of mass communication.The world of advertising is now growing very rapidly, making ad entrepreneurs must compete and be more creative in finding ideas. The purpose of this article is to find out the image of women in advertising aa an object of sexuality axe ad case studies. Image can have a strong emotional effect on people, and some imagery has historical significance. Sensuality becomes significant because often advertising gives a biased portrayal of a female figure, who rely solely on her body. An ad usually offers an image, which in the context of an ad language can be described as a mental picture of something that does not actually exist. Image has a very important role, as the definition of social relationships. Image or image displayed in this ad is the men who use this ax perfume will be a man who is liked by all women even angels can be enamored of the fragrance.